Essentials of organizational behavior - Robbins, Stephen P. (Pearson Education, 2016)
This book features only the most relevant topics in organizational behavior today, such as TQM; reengineering, technology; empowerment; declining employee loyalty; the Myers-Briggs Type Indicator; virtual and boundaryless organizations; 360-degree performance appraisals; diversity; globalization; ethics; and more.